Lifestyle and work of children and adolescents from Family Health Programs - Renata Cristina da Penha Silveira; Maria Lúcia do Carmo Cruz Robazzi (Universidade Federal de Goias, 2017)
The objective of this investigation was to analyze the lifestyle and work of children and adolescents registered in Family Health Programs of an inner city of São Paulo state. A quantitative, descriptive and cross-sectional study design, in which we interviewed children and adolescents using a socio-economic and labor questionnaire and the instrument Fantastic Lifestyle. We analyzed data using SPSS, version 19.0 of the 168 participants. Most were girls (51.8%), of mean age 12.79 years; Brown ethnicity (50%); living in popular housing (73.8%) and not studying (28.5%); 14% worked and 84 families received financial support from the Bolsa Família Program. There was no significant difference of lifestyle and work (Z=0.87; p=0.39). The study showed that although working, studying and helping their families with domestic tasks, interviewed participants had time to play and entertain themselves, and to feel happy; indicating that work did not influence their lifestyles.